The Relationship between Parental Approach and Anxiety - Abdulrahman Abdullah Al-Atram (Archives of Depression and Anxiety - Peertechz Publications, 2015)
Background and aim of the work: Parental approach with children has a considerable impact on this personality development process. The father/mother treatment of the child is the first human contact children experience, and will certainly leave an impact on their personality later on in life. This study came to emphasize the importance of parental approaches and their role in causing anxiety to female university students. It investigated the relationship between various developmental parental approaches and their psychological impact on female university students. Methodology  and  results: This  study  was  conducted  on  341  female  students  at  Majmaah University, Riyadh, Saudi Arabia. A Questionnaire with 57 statements was used. The data collected from the questionnaire were analyzed separately for approaches employed by the father and mother. It was seen that the correlation coefficient between anxiety level and father's aggression is 0.274, which indicated direct proportionality, demonstrating the relationship between those factors. This was with statistical significance of 0.013. The correlation coefficient between anxiety level and fathers' adequacy is -0.313, which indicates indirect proportionality indicating the negative relationship between those factors. This was with statistical significance of 0.016. When the same approaches followed by the mothers were considered the results obtained were very similar. Conclusion  and  recommendations: The study results indicated that the family is the first and most important social organization and has a huge impact on the personality of students. Therefore, parental approaches represent an important factor in the social, psychological, physical and mental development  of  children.  The  researcher  recommends  the  offering  of  awareness  and  mentoring program to parents, to educate them of the risks associated with inadequate approaches and their potential to increase anxiety levels and behavioral disorders among students.